An Empirical Study on Short Term and Long-term Consequences of Crude Oil on Economic Wellbeing of Indonesia by Applying Autoregressive Distributed Lag Model - Roespinoedji, Djoko; Roespinoedji, Roeshartono; Siam, Mohammed R.A.; Shamsudin, Mohd Farid (International Journal of Energy Economics and Policy, 2019)
Oil has been one of the primary wellsprings of Indonesia’s revenue, either from government spending plan or balance of payments purpose of perspectives. Because of supply and demand of oil on the planet market, prices of oil, either ICP, Brent UK, or WTI, had been decay of late. Oil prices and economic wellbeing are essential markers to see the achievement of Indonesia’s improvement execution. The utilization of oil as the world’s fundamental energy source when all is said in done and Indonesia specifically is driven by industrialization. The more ventures, the more prominent the energy resources required. In a similar setting, economic wellbeing will likewise expand oil demand. Oil has a strategic nature and is a vital ware that influences the world economy. Both oil exporters and merchants are probably going to feel the impacts of oil price advancements. Oil prices dropped pointedly since June 2014 finishing a four – year time of relative price strength. The size and speed of decay has been noteworthy yet not remarkable. This exploration plans to analyze the impact of crude oil prices on economic wellbeing in Indonesia. Data on crude oil prices and economic growth are yearly time series data stretching from 1987 to 2016. The aftereffects of co-integration tests demonstrate that there is no long-term connection between crude oil prices and economic wellbeing. In any case, the estimation of the autoregressive distributed lag (5.0) model demonstrates that in the short term, there is the impact of crude oil prices toward economic wellbeing. Keywords: Crude oil, oil price, growth, Autoregressive distributed lag model, Indonesia JEL Classifications: E31, A10 DOI: https://doi.org/10.32479/ijeep.8311